The Pledging Puzzle: How Can Revocable Promises Increase Charitable Giving? - Andreoni, James; Serra-Garcia, Marta (Management Science, 2021)
What is the value of pledges if they are often reneged upon? In this paper, we show—both theoretically and experimentally—that pledges can be used to screen donors and to better understand their motives for giving. In return, nonprofit managers can use the information they glean from pledges to better target future charitable giving appeals and interventions to donors, such as expressions of gratitude. In an experiment, we find that offering the option to pledge gifts induces self-selection. If expressions of gratitude are then targeted to individuals who select into pledges, reneging can be significantly reduced. Our findings provide an explanation for the potential usefulness of pledges.This paper was accepted by Yan Chen, decision analysis.